"This Time It's Different" Preparing for Release Through a Prison-Model of CoSA: A Phenomenological and Repertory Grid Analysis. (December 2019) - Kitson-Boyce, Rosie; Blagden, Nicholas; Winder, Belinda; Dillon, Gayle
Circles of support and accountability (CoSA) in the prison-model begin prior to the core members' release from prison and continue with them on release in to the community. The purpose of this study was to explore the expectations of release of those convicted of a sexual offense and how this develops during their participation in the prison sessions of CoSA. The research question was to consider how the prison-model of CoSA relates to the desistance of crime, in particular the phases of desistance developed by Gobbels, Ward, and Willis. Data were collected using both phenomenological interviews and repertory grids at two different time points; prior to starting the circle in prison ( n = 9) and just before release ( n = 5). The findings suggest the prison sessions provide a sense of support and "no longer being alone" often absent in those who sexually offend. The additional prison sessions enabled the participants to experience this during their approaching release date; a stressful period that was characterized by anxiety. Further research is now required to explore whether circles in the prison-model are able to encourage and reinforce the cognitive change required for desistance, enabling the core members to successfully manage their underlying anxieties surrounding societal stigmatization.